A new species of Metaspathius (Hymenoptera: Braconidae: Mesostoinae) from New Zealand. Issue 2 (3rd July 2019) - Quicke, Donald L.J.; Ward, Darren F.; Belokobylskij, Sergey A.; Butcher, Buntika A.
ABSTRACT: Metaspathius gorgasoma Quicke & Ward sp. n. is described from specimens collected from litter samples. It is mainly characterised by the mesoscutum being strongly declivous anteriorly, a derived morphological feature not found in congeners. Wing structure of the new species including shape and loss of posterior longitudinal flexion lines (claval furrows) of both fore and hind wings indicate its close relationship with M. hemipterus Belokobylskij from which it is distinguished.